Don't Take Chances - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet begins by raising awareness of the countless annual motor and domestic accident fatalities. Then discusses tips for using paint to avoid fire and physical injury in the home. For example, painted wooden surfaces are less likely to catch fire than unpainted wood, and bright and airy staircases are less likely to cause an injury than a darky dingy one; a remodeled home is a safe home. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Shellac; Paint materials; Linseed oil; Oilseeds; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint; Accidents--Prevention; Dwellings--Remodeling